Municipal-community relationship: a study on Kampar District Council perspective / Mariann Edwina Mariadass Lourdes, Edwin Michael and Eng May Chuen - Mariadass Lourdes, Mariann Edwina; Michael, Edwin; May Chuen, Eng (Faculty of Administrative Science and Policy Studies, 2012)
Local government is one of the government structures in Malaysia after federal government and state government, this government has a more direct connection to the people which in this case, the tax payers. Local Government Act 1976 empowers local government to implement its obligations as providing services that are related to sanitation, rubbish management, traffic management, roads and street lighting. We conduct research on the local government of Kampar and focus on the effectiveness of the Kampar District Council. The purpose of conducting this research is to determine whether the residents of Kampar are satisfied with the facilities and services that provided by Kampar District Council. We had did some research on what is local government and also identified the facilities and services that are supposing provided by Kampar District Council. Besides, this research also have the purpose of knowing if the Kampar District Council is doing their obligation and also identified what they promise under the time that is being set. Moreover, this research also let us know about the satisfactory level of the local residents in Kampar about the Kampar District Council based on the services and also the facilities provided varies according to occupation level. The research has been differentiated based on the occupation level which is the blue collar, white collar and also the unemployed. As a result, our findings about the satisfactory level were above average and there were some differences in the opinion of different level of job position being held.